Water Filtration Using Recycled Denim Fabrics for Daily Applications - AHMAD DANIEL MOHD NAFFREE; SITI ZAHARAH KUNCHI MON (Progress in Engineering Application and Technology, 2025)
This study investigates the use of three types of recycled denim fabrics coated with chitosan for household water filtration applications. Chitosan, a biopolymer known for its adsorption capabilities, was applied to enhance the removal of pollutants from raw water. Five layers of each denim type were stacked to form fabric filters. The filtration efficiency was assessed through turbidity and pH tests using river water as the test medium. Results showed that the chitosan-coated denim improved water clarity, with Denim 3 achieving 0 NTU turbidity and exhibiting no significant impact on pH. Although Denim 3 demonstrated high filtration efficiency, the filtration process occurred at a slower rate compared to other fabrics. These results indicate that the combination of chitosan coating on denim can be used as a cheap and sustainable option to treat small water volumes in a decent way, particularly in areas with limited access to clean water.